Social transformation if local communities through community-based ecotourism for sustainable livelihoods in lower Kinabatangan , Sabah - Velan Kunjuraman (2020)
Community-based ecotourism (CBE) projects in developing countries are often claimed as a means to achieve sustainable livelihood for the local communities in rural areas, particularly in Malaysia. On the other hand, CBE is also continuously promoted as economic and local community development tools by the Malaysian government and several policies have been formulated to achieve these missions. However, empirical studies related to social transformations of local communities through CBE projects in Malaysia are scarce in order to explore the extent CBE projects have successfully transformed the local communities upon their continuous active engagement. For this reason, two CBE projects in Lower Kinabatangan, Sabah, which have been managed by the local communities since the 1990s, were selected as case studies. The aim of this study is to examine the social transformations of local communities through CBE projects in the Sukau and Bilit villages of Lower Kinabatangan in the economic, socio-cultural and environmental aspects. The qualitative research approach using the case study research strategy was adopted in this study. In order to collect primary data, methods such as in-depth interviews, direct observation and secondary data resources were applied in this study. From the qualitative analysis of the two cases, the study discovered that CBE project participants in Sukau and Bilit have successfully transformed their lives in economic, socio-cultural and environmental aspects through their active participation in CBE projects. The study noted that the positive social transformations of CBE in Sukau and Bilit outnumbered the negative social transformations of CBE. The success of these social transformation aspects have contributed to the livelihood enhancement of the local communities in the study sites. However, CBE as a means for sustainable livelihood in both villages is still unclear and questionable due to the negative social transformations of CBE and the challenges faced by the local communities in ecotourism operation. The thesis concludes that CBE is an appropriate pathway to enhance local communities’ livelihoods in both study sites but recognition of the identified challenges is required and they need to be addressed. Thus, this study has recommended proactive measures and appropriate policies are required to ensure the sustainability of the CBE projects in both villages by the relevant stakeholders in Sabah, Malaysia. Thus, this study has recommended proactive measures and appropriate policies to ensure the sustainability of the CBE projects in both villages by the relevant stakeholders in Sabah, Malaysia.